Cystic Endometrial Hyperplasia (CEH) in Coati (Nasua nasua): Treatment with Ovariosalpingohysterectomy - Flores Moraes, Lilian; Morel, Ana Paula; Depelegrin, Carolina; Ribeiro dos Santos, Vinícius; Guarise, Raquel; Izabel Pedra Sogari, Maria; Garcia, Leila (Acta Scientiae Veterinariae, 2026)
Background: Coatis (Nasua nasua) are omnivorous and diurnal animals belonging to the order Carnivora and family Procyonidae. Despite their wide distribution across South America and numerous free-living and captive populations throughout Brazil, clinical reports on these animals are scarce. Consequently, the prevalence and characteristics of disorders affecting the species in captivity remain poorly understood. This report highlights the importance of thorough monitoring of these animals by professionals, particularly regarding subtle behavioral changes in response to illness. Case: One female coati with cystic endometrial hyperplasia was admitted to the Canoas Municipal Zoo, in southern Brazil. The animal, under human care, had a history of melengestrol acetate implantation, and exhibited alopecia, dry coat, and cachexia. A comprehensive examination was performed, including a complete blood count, biochemical profile, and ultrasonography. imaging revealed diffuse cystic alterations in the uterine body and horns, suggestive of cystic endometrial hyperplasia. The liver showed slightly reduced echogenicity, and the kidneys displayed small punctiform images scattered throughout the parenchyma, along with mineralization in some pelvic recesses, suggesting hepatic toxemia and dystrophic mineralization of the kidneys. The treatment of choice was ovariohysterectomy, performed according to techniques recommended for dogs and cats. The animal was anesthetized with ketamine (10 mg/kg), midazolam (0.5 mg/kg), and methadone (0.2 mg/kg). After 15 min, pre-oxygenation with 100% oxygen at 2 L/min was initiated and the ulnar vein was cannulated using a 24G catheter. Induction was achieved with intravenous propofol (4 mg/kg). Intubation was performed using an endotracheal tube. A Baraka system was connected to the circuit and delivered oxygen at 2 L/min with isoflurane vaporized at 1%. The animal was placed in lateral recumbency for an ultrasound-guided quadratus lumborum block using bupivacaine (2 mg/kg at 0.5%) bilaterally. Subsequently, the animal was positioned in dorsal recumbency and abdominal trichotomy and antisepsis with alcohol and chlorhexidine were performed. Nylon sutures were used for all layers with intradermal suturing and no external knots. Surgical glue was also applied as a preventive measure. In the immediate postoperative period, the animal received meloxicam (0.1 mg/kg) and dipyrone (25 mg/kg) subcutaneously, along with amoxicillin (22 mg/kg). The animal recovered well, without complications after the procedure. The removed organs were fixed in 10% buffered formalin and analyzed. Macroscopic evaluation revealed that the uterine horns had multiple cystic areas containing small amounts of brown mucous secretions. The inner layer of the myometrium showed multifocal thickening with infiltration of islands of ruptured endometrial glands, associated with the proliferation of smooth muscle bundles. These findings confirmed our diagnosis of cystic endometrial hyperplasia and indicated concomitant adenomyosis. Discussion: The ideal choice of surgical intervention should take into account not only the severity of the disorder, but also the potential for aggression from other group members in cases of shared enclosures. The development of pyometra and adenocarcinoma resulting from melengestrol acetate use has been documented in N. Nasua as well as in felids, canids, and primates, raising concerns about use of this contraceptive method. Case reports on wildlife are vital for understanding their physiological parameters and predispositions to disease. Moreover, this report highlights the importance of routine examinations of captured wild animals, as their subtle behaviors often mask underlying illnesses. Keywords: procyonids, ovariohysterectomy, ultrasonography, wild animals, captivity. Título: Hiperplasia endometrial cística (HCE) em Quati (Nasua nasua): tratamento com Ovariohisterectomia Descritores: procionídeos, ovariohisterectomia, ultrassonografia, animais selvagens, cativeiro.